MEMAKSIMALKAN FUNGSI SUNGLASSES UNTUK PENCEGAHAN DINI KATARAK - Sandi Agung Itamurti; M.Wahyu Budiana; Murni Marlina Simarmata (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
Cataract is an eye disease that creates hazy eye lenses. This condition often happens due to, among other, too much subjection to ultra violet light without the right sunglasses. Thus, early prevention of cataracts can be conducted by using sunglasses when being outside the room and being in long-term exposure to sunlight. This study aimed to highlight proper ways using sunglases in order to prevent cataract as early as possible.Using librabry research, primarily a book book by Clifford W. Brooks and Irvin M. Borish titled “ System for Ophthalmic Dispensing”, this study discussed the proble and suggest some solutions with desctiptive method.